Nursing Degree Curriculum: Differences and Similarities Between 15 European Countries - Celeste Antão; Bruna Santos; Nelson Santos; Hélder Fernandes; Bárbara Barroso; Cristina Oana Mǎrginean; Helena Pimentel (Nursing Reports)
This study explores the curriculum of Nursing Bachelor’s degrees across 15 European countries, aiming to describe nursing course curricula and admission requirements and to identify differences and similarities in the implementation of the Bologna Process. The research employs a qualitative and documentary methodology, analyzing curricula from selected higher education institutions involved in the Erasmus+ “Innovative Skills for Nurses” project. The findings reveal variations in the duration of training, with some countries adopting 3-year (180 ECTS) programs, while others require 4-year (240 ECTS) programs. Furthermore, discrepancies were found in the balance between theoretical and clinical education, as well as the availability of optional subjects. Countries with longer training programs tend to offer more consolidated practices and greater alignment with Bologna’s principles, fostering better professional outcomes. The study highlights the challenges posed by non-standardized training durations and their impact on mobility and employability of nursing professionals. These findings may inform future discussions on harmonizing nursing education across Europe to ensure consistency in quality and professional competencies.